Study of Wireless Sensor Network - Sriwas, Anjani; Patel, Rakesh; Patel, Mili (International Journal For Research In Advanced Computer Science And Engineering, 2016)
As wireless sensor technology improves; an increasing number of organizations are using it for a wide range of purpose, Wireless Sensor Networks (WSN) are used in variety of fields which includes military, healthcare, environmental, biological, home and other commercial applications. With the huge advancement in the field of embedded computer and sensor technology, Wireless Sensor Networks (WSN), this is composed of several thousands of sensor nodes which are capable of sensing, and relaying the collected information, have made remarkable impact everywhere. This paper presents an overview of the various research issues in WSN based applications.